2002
DOI: 10.1074/jbc.c200303200
|View full text |Cite
|
Sign up to set email alerts
|

A Missense Mutation in Kynurenine Aminotransferase-1 in Spontaneously Hypertensive Rats

Abstract: Spontaneously hypertensive rats (SHR) are the most extensively used animal model for genetic hypertension, increased stroke damage, and insulin resistance syndromes; however, the identification of target genes has proved difficult. SHR show elevated sympathetic nerve activity, and stimulation of the central blood pressure control centers with glutamate or nicotine results in exaggerated blood pressure responses, effects that appear to be genetically determined. Kynurenic acid, a competitive glutamate antagonis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
47
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 25 publications
2
47
0
Order By: Relevance
“…By genetic analysis, a missense mutation (E61G) in the KAT I gene was identified in spontaneously hypertensive rats and shown to lead to reduced KAT I on May 12, 2018 by guest http://mcb.asm.org/ enzymatic activity and higher blood pressure (29,34). Our previous study dealing with structural characterization of hKAT I revealed that the evolutionarily conserved Glu27 residue (i.e., Glu61 in the full-length sequence of KAT I), positioned at the C terminus of the H1 helix, is a pivotal residue in fixing the helix in the observed conformations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By genetic analysis, a missense mutation (E61G) in the KAT I gene was identified in spontaneously hypertensive rats and shown to lead to reduced KAT I on May 12, 2018 by guest http://mcb.asm.org/ enzymatic activity and higher blood pressure (29,34). Our previous study dealing with structural characterization of hKAT I revealed that the evolutionarily conserved Glu27 residue (i.e., Glu61 in the full-length sequence of KAT I), positioned at the C terminus of the H1 helix, is a pivotal residue in fixing the helix in the observed conformations.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to its role as an excitatory amino acid antagonist, KYNA is also involved in the control of cardiovascular function by acting at the rostral ventrolateral medulla of the central nervous system (8). Spontaneously hypertensive rats, the most widely used animal model for studying genetic hypertension, have abnormally low KYNA levels in the area of the central nervous system that tunes physiological blood pressure (29,34).…”
mentioning
confidence: 99%
“…This defect has been associated with abnormally low KA levels in the central nervous system-specific districts tuning physiological blood pressure (49,50). Sequencing analysis revealed the presence of a single point mutation in the KAT-I gene in all of the examined spontaneously hypertensive rats, leading to the substitution of a glutamate by a glycine at position 61 in the enzyme (51). Remarkably, the resulting mutated protein showed a severely reduced enzymatic activity, hinting at the key role of position 61 in catalysis (51).…”
Section: Resultsmentioning
confidence: 99%
“…Within the renal cortex and medullary DNA arrays, we identified marker genes that were highly expressed in either renal cortex or medulla but were expressed by at least a 10-fold lower amount in glomeruli and were unaffected by diet and age. We used kynurenine aminotransferase as a marker of proximal tubules (34). We used claudin 16, an epithelial tight junction protein present in the thick ascending limb of Henle but not in glomerulus (35), as a medullary marker.…”
Section: Dna Microarray Analysismentioning
confidence: 99%